STRATEGI DIFERENSIASI PRODUK, DIVERSIFIKASI PRODUK, HARGA JUAL DAN KAITANNYA TERHADAP PENJUALAN PADA INDUSTRI KERAJINAN ROTAN DI KOTA PALEMBANG - Yuni Tarida (Department of Development Economics, Universitas Sriwijaya, 2012)
This study was aimed at finding out the relationships between the product differential strategy and product diversification and the sales at rattan craft industry in Palembang. The results of the study showed that only the best quality product which dominated the best sellers in the market place. It was because the buyers were willing to pay more price for better product. Product diversification had a significant relationship with the sales on which 5 manufacturers or 41,66 % of the whole turnovers were controlled by manufacturers who diversified the product. In terms of product diversification, the manufacturers who had large amount of monthly capital and diversified the product, the sales turnovers tended to be lower than those who produced single type of product. It was because the manufacturers produced low price small scale product and the buyers little interests to the products. Keywords: rattan craft industry, product differences, product diversification, sale.